Intradiffusion mass transfer during drying of slag gravel raw granule - Barna, Iryna; Gumnytskyi, Yaroslav; Atamanyuk, Volodymyr (Publishing House of Lviv Polytechnic National University, 2013)
Intradiffusion mass transfer during drying of a single raw granule of slag gravel has been investigated. The physical model of moisture distribution in the single particle during its drying in the second period has been suggested. The process of intradiffusion mass transfer during drying slag gravel raw granule has been described mathematically. The effect of intradiffusion coefficient on the temperature has been studied. Досліджено внутрішньодифузійне масоперенесення під час сушіння одинарної сирцевої гранули шлакового гравію. Запропоновано фізичну модель розподілу вологи в одинарні частинці під час її сушіння у другому періоді. Математично описано процес внутрішньодифузійного масоперенесення під час сушіння сирцевої гранули шлакового гравію. Досліджено залежність коефіцієнта внутрішньої дифузії від температури.
Внутрішньодифузійне масоперенесення під час сушіння сирцевої гранули шлакового гравію
Keywords: intradiffusion coefficient; drying kinetics; moisture content; raw granule; moisture content gradient; коефіцієнт внутрішньої дифузії; кінетика сушіння; вологовміст; сирцева гранула; градієнт вологовмісту